168 DEVELOPMENT OF A PREOPERATIVE PROTOCOL TO ENHANCE OPERATING ROOM TEAM FUNCTION: THE SAFETY PREP™. (1st January 2005) - Paige, J. T.; Kozmenko, V.; Chauvin, S.; Hilton, C. W.; O'Leary, J. P.
Abstract : Introduction: According to the Institute of Medicine (IOM), medical errors account for nearly 98, 000 deaths in the United States each year. Given that almost half of all adverse events in hospitalized patients are associated with an operation, the Joint Committee on Accreditation of Healthcare Organizations (JCAHO) has recently instituted The Universal Protocol for Preventing Wrong Site, Wrong Procedure, Wrong Person SurgeryTM. We have developed a preoperative protocol, the SAFETY PrepTM, designed to promote better operating room (OR) team functioning while fulfilling the requirements of the JCAHO Universal Protocol. Methods: We established a set of criteria that took into account both OR requirements and human factors theory in developing the SAFETY PrepTM. Key components included compatibility with the JCAHO Universal Protocol, simplicity in structure, adaptability, ease of use, and acceptability. We piloted the protocol on seven clinicians. Results: The SAFETY PrepTM is a mnemonically driven protocol using metacognitive principles designed to make OR team members more conscious about their thought processes. It is divided into 5 major phases: 1. preliminaries, during which team members introduce themselves; 2. patient, during which the patient condition and history is reviewed; 3. procedure, during which the proposed procedure is verified; 4. plan, during which the major steps of the operation are reviewed; and 5. possibilities, during which contingencies are made for potential problems. The SAFETY PrepTM fulfills all the requirements of the Universal Protocol and is designed to serve as a structured "time out" before beginning an operation. When piloted on seven clinicians, the protocol showed promise as a useful device to promote improved OR team functioning. Conclusions: The SAFETY PrepTM is a preoperative protocol based on human factors principles that allows OR team members to "think about their thinking." In this way, it should help OR teams function more efficiently and effectively. By doing so, we believe that the SAFETY PrepTM will help promote error reduction in the OR. We plan to test this hypothesis through OR team training in the SAFETY PrepTM using an advanced simulation environment.